(3x+2)(3x-4)=(2x+3)(3x-1)+(3x+1)(x-4) Как решить?

(3x+2)(3x-4)=(2x+3)(3x-1)+(3x+1)(x-4) Как решить?
Гость
Ответ(ы) на вопрос:
Гость
(3x+2)(3x-4)=(2x+3)(3x-1)+(3x+1)(x-4) 9х²-12х+6х-8=6х²-6х+9х-3+3х²-12х+х-4 9х²-6х²-3х²-12х+6х-6х-9х+12х-х=8-3-4 -10х=1 х= -0.1
Гость
9х²-12х+6х-8=6х²-2х+9х-3+3х²-12х+х-4 9х²-6х-8=9х²-4х-7 9х²-9х²-6х+4х=-7+8 -2х=1 х=1:(-2) х=-1/2=-0,5 Проверка: (3*(-0,5)+2)(3*(-0,5)-4)=(2*(-0,5)+3)(3*(-0,5)-1)+(3*(-0,5)+1)(-0,5-4) (-1,5+2)(-1,5-4)=(-1+3)(-1,5-1)+(-1,5+1)(-4,5) 0,5*(-5,5)=2*(-2,5)+(-0,5)*(-4,5) -2,75=-5+2,25 -2,75=-2,75 Всё верно! Ответ: х=-0,5
Не нашли ответ?
Ответить на вопрос
Похожие вопросы